Cutting tool
By using the alternating layer on the cutting tool, the use of W (C1-Nana) X and ALCV1-CN alternate layers can be used to solve the problem of short life of existing cutting tools under high temperature conditions, and the long life of tools has been achieved. And efficient cutting performance.
Patent Information
- Application Number
- CN202380042863.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-17
- Publication Date
- 2025-01-28
AI Technical Summary
Existing cutting tools have short lifespans under high temperature conditions, making it difficult to meet the high-speed, high-efficiency and high-precision cutting processing needs. Especially when dealing with difficult-to-cut materials, the tool's wear resistance and oxidation resistance are insufficient.
The alternating layer of the alternating layer of the first unit layer and the second unit layer, the first unit layer consists of W (C1 -Ana) X, the second unit layer consists of ALCV1-CN, and the physical steam plating method is formed. Overwing, improving the wear resistance and oxidation resistance of the tool.
Under the condition of high knife tip temperature, the life of the cutting tool is significantly extended, which can maintain high accuracy in high -speed and high -efficiency cutting processing and reduce waste and energy consumption.
Smart Images

Figure CN119384329A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to cutting tools. Background Art
[0002] Conventionally, a cutting tool including a substrate and a coating disposed on the substrate has been used for cutting processing (Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application No. 2022-512808 Summary of the invention
[0006] A cutting tool according to one embodiment of the present disclosure includes a substrate and a coating disposed on the substrate, wherein:
[0007] The coating comprises a first layer,
[0008] The first layer is composed of alternating layers formed by alternatingly stacking first unit layers and second unit layers,
[0009] The first unit layer has a hexagonal crystal structure,
[0010] The first unit layer is composed of W(C 1-a N a ) x constitute,
[0011] The a is greater than or equal to 0.3 and less than or equal to 0.8,
[0012] The x is greater than or equal to 0.8 and less than or equal to 1.2,
[0013] The second unit layer is composed of Al c V 1-c N constitutes,
[0014] The c is greater than or equal to 0.40 and less than or equal to 0.80. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a schematic enlarged cross-sectional view of an example of the cutting tool according to the first embodiment.
[0016] Figure 2 This is a schematic enlarged cross-sectional view of another example of the cutting tool according to the first embodiment.
[0017] Figure 3 This is a schematic enlarged cross-sectional view of another example of the cutting tool according to the first embodiment.
[0018] Figure 4This is a schematic enlarged cross-sectional view of another example of the cutting tool according to the first embodiment.
[0019] Figure 5 This is a diagram for explaining an example of the ratio of the thickness of the first unit layer to the thickness of the second unit layer.
[0020] Figure 6 It is a schematic enlarged cross-sectional view of an example of a cutting tool according to the second embodiment.
[0021] Figure 7 It is a schematic enlarged cross-sectional view of another example of the cutting tool according to the second embodiment.
[0022] Figure 8 It is a schematic enlarged cross-sectional view of another example of the cutting tool according to the second embodiment.
[0023] Fig. 9 It is a schematic enlarged cross-sectional view of another example of the cutting tool according to the second embodiment.
[0024] Fig.10 This is a diagram for explaining an example of the ratio of the thickness of the first unit layer to the thickness of the third unit layer.
[0025] Fig.11 It is a schematic cross-sectional view of a cathodic arc ion plating device used in Examples.
[0026] Fig.12 yes Fig.11 A schematic top view of a cathodic arc ion plating apparatus is shown. DETAILED DESCRIPTION
[0027] [Problems to be Solved by the Present Disclosure]
[0028] Cutting also plays a major role in manufacturing technology, and there is a constant demand for technological evolution and further sophistication. In cutting technology, high-speed, high-efficiency, high-precision processing and ultra-fine processing are basically required. As a recent trend, there is a trend of difficult cutting of cut materials, and it is also required to respond to this situation. On this basis, in the field of cutting, in order to achieve a sustainable and better world by 2030, the attention to SDGs (Sustainable Development Goals) has been increasing in recent years. Sustainable development refers to the construction of a social foundation that can withstand the threat of nature without damaging the resources needed by future generations. Through the improvement of cutting technology, it can be expected that the environmental burden will be reduced by reducing the power saving during product manufacturing brought about by reducing the process and reducing the waste associated with cutting. Based on this background, in order to extend the life of the tool, the development of coated tool materials with high high temperature hardness and both hardness and toughness is directed.
[0029] As a type of coating tool material, a nitride film with Al and V as the main components has been proposed (Patent Document 1). From the perspective of SDGs and global environmental protection, there is a trend that the tip temperature of the cutting tool during cutting becomes high temperature due to the requirements for dry machining without the use of cutting oil, the higher cutting speed to improve machining efficiency, and the diversification of cut materials, especially in the fields of aircraft and medicine, and the increase in the cutting of heat-resistant alloys and titanium alloys, which are known as difficult-to-cut materials. If the tip temperature becomes high, the life of the cutting tool becomes extremely short. Therefore, a cutting tool that can show excellent tool life even under such harsh cutting conditions is required.
[0030] [Effects of the present disclosure]
[0031] According to the present disclosure, it is possible to provide a cutting tool having a long tool life even in cutting processing performed under conditions where the cutting edge temperature is high.
[0032] [Description of Embodiments of the Present Disclosure]
[0033] First, embodiments of the present disclosure will be described by way of examples.
[0034] (1) A cutting tool according to one aspect of the present disclosure includes a substrate and a coating disposed on the substrate, wherein:
[0035] The coating comprises a first layer,
[0036] The first layer is composed of alternating layers formed by alternatingly stacking first unit layers and second unit layers,
[0037] The first unit layer has a hexagonal crystal structure,
[0038] The first unit layer is composed of W(C 1-a N a ) x constitute,
[0039] The a is greater than or equal to 0.3 and less than or equal to 0.8,
[0040] The x is greater than or equal to 0.8 and less than or equal to 1.2,
[0041] The second unit layer is composed of Al c V 1-c N constitutes,
[0042] The c is greater than or equal to 0.40 and less than or equal to 0.80.
[0043] According to the present disclosure, it is possible to provide a cutting tool having a long tool life even in cutting processing performed under conditions where the cutting edge temperature is high.
[0044] (2) In the above (1), in the first unit layer and the second unit layer adjacent to the first unit layer, a ratio λ2 / λ1 of a thickness λ2 μm of the second unit layer to a thickness λ1 μm of the first unit layer is greater than or equal to 1.0 and less than or equal to 5.0. Thus, the cutting tool can have a longer tool life.
[0045] (3) In addition to the above (1) or (2),
[0046] The average thickness of the first unit layer is greater than or equal to 0.002 μm and less than or equal to 0.2 μm,
[0047] The average thickness of the second unit layer is greater than or equal to 0.002 μm and less than or equal to 0.2 μm.
[0048] As a result, the cutting tool can have a longer tool life.
[0049] (4) In addition to any one of the above (1) to (3),
[0050] The coating further includes a second layer disposed between the substrate and the first layer.
[0051] The composition of the second layer is the same as the composition of the first unit layer or the composition of the second unit layer.
[0052] As a result, the cutting tool can have a longer tool life.
[0053] (5) Alternatively, based on (4) above,
[0054] The composition of the second layer is the same as that of the first unit layer,
[0055] The second layer is thicker than the first unit layer.
[0056] As a result, the cutting tool can have a longer tool life.
[0057] (6) Alternatively, based on (4) above,
[0058] The composition of the second layer is the same as the composition of the second unit layer,
[0059] The second layer has a thickness greater than that of the second unit layer.
[0060] As a result, the cutting tool can have a longer tool life.
[0061] (7) In addition to any one of the above (1) to (6),
[0062] The coating further includes a third layer disposed on the first layer on the opposite side of the substrate.
[0063] The third layer is composed of AlVCN.
[0064] As a result, the cutting tool can have a longer tool life.
[0065] (8) A cutting tool according to another embodiment of the present disclosure includes a substrate and a coating disposed on the substrate, wherein:
[0066] The coating comprises a layer 1A,
[0067] The 1A layer is composed of an alternating layer in which the first unit layer and the third unit layer are alternately stacked.
[0068] The first unit layer has a hexagonal crystal structure,
[0069] The first unit layer is composed of W(C 1-a N a ) x constitute,
[0070] The a is greater than or equal to 0.3 and less than or equal to 0.8,
[0071] The x is greater than or equal to 0.8 and less than or equal to 1.2,
[0072] The third unit layer is composed of Al d V 1-d-e M e N constitutes,
[0073] The M is silicon, boron, yttrium, cerium or lanthanum,
[0074] The d is greater than or equal to 0.40 and less than or equal to 0.80,
[0075] The above-mentioned e is greater than 0 and less than 0.05.
[0076] According to the present disclosure, it is possible to provide a cutting tool having a long tool life even in cutting processing performed under conditions where the cutting edge temperature is high.
[0077] (9) Alternatively, based on (8) above,
[0078] In the first unit layer and the third unit layer adjacent to the first unit layer,
[0079] A ratio λ3 / λ1 of a thickness λ3 μm of the third unit layer to a thickness λ1 μm of the first unit layer is greater than or equal to 1.0 and less than or equal to 5.0.
[0080] As a result, the cutting tool can have a longer tool life.
[0081] (10) In the above (8) or (9), M may be silicon.
[0082] As a result, the cutting tool can have a longer tool life.
[0083] (11) In the above (8) or (9), M may be boron.
[0084] As a result, the cutting tool can have a longer tool life.
[0085] (12) In addition to any one of the above (8) to (11),
[0086] The average thickness of the first unit layer is greater than or equal to 0.002 μm and less than or equal to 0.2 μm,
[0087] The average thickness of the third unit layer is greater than or equal to 0.002 μm and less than or equal to 0.2 μm.
[0088] As a result, the cutting tool can have a longer tool life.
[0089] (13) In addition to any one of the above (8) to (12),
[0090] The coating further includes a 2A layer disposed between the substrate and the 1A layer,
[0091] The composition of the 2A layer is the same as the composition of the first unit layer or the composition of the third unit layer.
[0092] As a result, the cutting tool can have a longer tool life.
[0093] (14) Alternatively, based on the above (13),
[0094] The composition of the 2A layer is the same as that of the first unit layer,
[0095] The thickness of the 2A layer is thicker than that of the first unit layer.
[0096] As a result, the cutting tool can have a longer tool life.
[0097] (15) Alternatively, based on the above (13),
[0098] The composition of the 2A layer is the same as the composition of the third unit layer,
[0099] The thickness of the 2A layer is thicker than that of the third unit layer.
[0100] As a result, the cutting tool can have a longer tool life.
[0101] (16) In addition to any one of the above (8) to (15),
[0102] The coating further includes a 3A layer provided on the side of the 1A layer opposite to the substrate,
[0103] The 3A layer is composed of AlVMeCN,
[0104] The Me is silicon, boron, yttrium, cerium or lanthanum.
[0105] As a result, the cutting tool can have a longer tool life.
[0106] [Details of the embodiments of the present disclosure]
[0107] Hereinafter, specific examples of the cutting tool disclosed in the present invention will be described with reference to the accompanying drawings. In the drawings disclosed in the present invention, the same reference numerals represent the same parts or equivalent parts. In addition, the dimensional relationships such as length, width, thickness, depth, etc. are appropriately changed for the clarity and simplification of the drawings, and do not necessarily represent the actual dimensional relationships.
[0108] In the present disclosure, expressions in the format of “A to B” refer to the upper and lower limits of a range (i.e., greater than A and less than B). When there is no unit recorded in A and only a unit is recorded in B, the unit of A is the same as that of B.
[0109] In the present disclosure, when a compound or the like is represented by a chemical formula, unless the atomic ratio is particularly limited, all conventionally known atomic ratios are included, and the atomic ratio is not necessarily limited to the atomic ratio within the stoichiometric range.
[0110] In the present disclosure, when more than one numerical value is recorded as the lower limit and the upper limit of the numerical range, a combination of any numerical value recorded in the lower limit and any numerical value recorded in the upper limit is also disclosed. For example, when more than a1, more than b1, and more than c1 are recorded as the lower limit, and less than a2, less than b2, and less than c2 are recorded as the upper limit, more than a1 and less than a2, more than a1 and less than b2, more than a1 and less than c2, more than b1 and less than a2, more than b1 and less than b2, more than b1 and less than c2, more than c1 and less than a2, more than c1 and less than b2, more than c1 and less than c2 are disclosed.
[0111] [First embodiment: cutting tool (1)]
[0112] use Figure 1 to Figure 5 A cutting tool according to an embodiment of the present disclosure will be described.
[0113] A cutting tool 1 according to one embodiment of the present disclosure (hereinafter also referred to as a “first embodiment”) includes a substrate 2 and a coating 3 disposed on the substrate 2, wherein:
[0114] The coating 3 comprises a first layer 13,
[0115] The first layer 13 is composed of alternating layers in which the first unit layers 12 and the second unit layers 15 are alternately stacked.
[0116] The first unit layer 12 has a hexagonal crystal structure.
[0117] The first unit layer 12 is composed of W(C 1-a N a ) x constitute,
[0118] a is 0.3 or more and 0.8 or less,
[0119] x is 0.8 or more and 1.2 or less,
[0120] The second unit layer 15 is made of Al c V 1-c N constitutes,
[0121] c is 0.40 or more and 0.80 or less.
[0122] The cutting tool 1 of the first embodiment can have a long tool life even in cutting processing performed under the condition of high cutting edge temperature. The reason for this is presumably as follows.
[0123] The first unit layer 12 is composed of W (C 1-a N a ) xThe first unit layer 12 contains C (carbon), so the friction coefficient at the contact interface with the cut material is reduced, which can reduce the cutting resistance. 1-a N a ) x Since N (nitrogen) is included, the heat resistance is improved by about 150°C compared to WC. As a result, the first layer including the first unit layer can improve the adhesion resistance, sliding property and wear resistance in processing where the cutting edge becomes high temperature during dry cutting, etc. Therefore, the tool life of the cutting tool including the first layer is improved.
[0124] The second unit layer 15 is made of Al c V 1-c N. The second unit layer 15 contains Al. Since Al is easily oxidized, the coating containing the second unit layer 12 has a tendency to easily form a dense oxide layer composed of Al2O3 on the surface side of the first layer 13. As a result, the thermal blocking property and oxidation resistance of the first layer 13 can be improved. Therefore, the tool life of the cutting tool containing the first layer 13 is improved.
[0125] The second unit layer 15 is oxidized during cutting to generate V2O5, which is an oxide of V. V2O5 has a melting point of 690°C, so it softens at the temperature during cutting and functions as a lubricant, which can reduce the friction coefficient on the tool rake face.
[0126] The first layer 13 is composed of alternating layers in which the first unit layer 12 and the second unit layer 15 are alternately stacked. The composition and lattice are discontinuous at the interface between the first unit layer 12 and the second unit layer 15. Therefore, when cracks are generated from the surface of the coating 3 during cutting, the progress of the cracks can be suppressed at the interface. In the coating including the first layer, chipping and defects are suppressed. Therefore, the tool life of the cutting tool including the first layer 13 is improved.
[0127] <Cutting tools>
[0128] like Figure 1 as well as Figure 2 As shown, a cutting tool 1 according to an embodiment of the present invention comprises a substrate 2 and a coating 3 disposed on the substrate 2. The coating 3 can cover at least the portion of the substrate 2 that participates in cutting. The coating 3 can also cover the entire surface of the substrate 2. Even if the composition of the coating 3 is partially different, it does not deviate from the scope of this embodiment. In this specification, the portion of the substrate 2 that participates in cutting refers to an area on the surface of the substrate 2 that is at least within 50 μm, within 100 μm, or within 300 μm from the edge line of the blade tip.
[0129] The cutting tool 1 of this embodiment can be suitably used as a cutting tool 1 such as a drill, an end mill, an indexable cutting insert for a drill, an indexable cutting insert for an end mill, an indexable cutting insert for milling, an indexable cutting insert for turning, a metalworking saw, a gear cutting tool, a reamer, and a tap.
[0130] <Base Material>
[0131] As the substrate 2, any substrate known in the past can be used. For example, the substrate 2 can be composed of any one of cemented carbide (WC-based cemented carbide, cemented carbide containing WC and Co, cemented carbide with carbonitrides such as Ti, Ta, and Nb added to WC and Co, etc.), cermet (cermet with TiC, TiN, TiCN, etc. as the main component), high-speed steel, ceramic (titanium carbide, silicon carbide, silicon nitride, aluminum nitride, aluminum oxide, etc.), cubic boron nitride sintered body, or diamond sintered body.
[0132] The substrate 2 can be, in particular, a WC-based cemented carbide or a cermet (in particular, a TiCN-based cermet). Since WC-based cemented carbide or cermet has an excellent balance of hardness and strength, in particular at high temperatures, when used as the substrate 2 of the cutting tool 1, it can contribute to the long life of the cutting tool 1.
[0133] <Lamination>
[0134] The coating 3 of the first embodiment includes the first layer 13. The coating 3 covers the substrate 2, thereby improving various properties of the cutting tool 1 such as wear resistance and chipping resistance, thereby extending the life of the cutting tool 1.
[0135] The coating 3 may further include other layers in addition to the first layer 13. As other layers, for example Figure 3 as well as Figure 4 As shown, the second layer 16 disposed between the substrate 2 and the first layer 13 and the third layer 14 provided on the side of the first layer 13 opposite to the substrate 2 are exemplified.
[0136] The overall thickness of the coating 3 may be 0.4 μm or more and 15 μm or less. If the overall thickness of the coating 3 is 0.4 μm or more, the effect of extending the life of the cutting tool 1 by providing the coating 3 is easily obtained. On the other hand, if the overall thickness of the coating 3 is 15 μm or less, it is difficult to cause cracks in the coating 3 at the initial stage of cutting, and the life of the cutting tool 1 can be extended.
[0137] The thickness of the entire coating 3 can be measured by observing the cross section of the coating 3 using a scanning electron microscope (SEM). The specific measurement method is as follows. Cut the cutting tool 1 in the direction along the normal line of the surface of the coating 3 to prepare a cross-sectional sample. Observe the cross-sectional sample using an SEM. The observation magnification is set to 5000 to 10000 times, and the measurement field of view is set to 100 to 500 μm. 2 In one field of view, the thickness widths of three locations of the coating 3 are measured, and the average value of the thickness widths of the three locations is calculated. This average value corresponds to the thickness of the coating 3. The thickness of each layer described below is measured by the same method unless otherwise specified.
[0138] The absolute value of the compressive residual stress of the coating 3 may be 6 GPa or less. The compressive residual stress of the coating 3 refers to a type of internal stress (intrinsic strain) present in the entire coating 3, and refers to stress represented by a "-" (negative) numerical value (unit: "GPa" is used in this embodiment). Therefore, the concept of a large compressive residual stress means that the absolute value of the numerical value becomes larger, and the concept of a small compressive residual stress means that the absolute value of the numerical value becomes smaller. That is, the absolute value of the compressive residual stress of 6 GPa or less means that the compressive residual stress of the coating 3 is greater than -6 GPa and less than 0 GPa.
[0139] If the compressive residual stress of the coating 3 is 0 GPa or less, it is easy to suppress the progress of cracks generated from the outermost surface of the coating 3. On the other hand, if the absolute value of the compressive residual stress is 6 GPa or less, the stress is moderate and it is easy to suppress the coating 3 from peeling off from the edge of the cutting tool 1 before cutting starts.
[0140] The compressive residual stress of the coating 3 was measured by sin 2 The measurement was performed by the ψ method (see "X-ray Stress Measurement Method" (Japan Society for Materials Science, published by Yokendo Co., Ltd. in 1981) pp. 54 to 66).
[0141] The first unit layer 12 may have a hexagonal crystal structure. If the first unit layer 12 has a hexagonal crystal structure, the wear resistance of the coating 3 is improved. The second unit layer 15 may include a cubic crystal structure. If the second unit layer 15 has a cubic crystal structure, the hardness of the coating 3 is improved. The crystal structure of each layer in the coating 3 can be analyzed by an X-ray diffraction device known in the art.
[0142] When the hardness of the coating 3 is greater than 30 GPa and less than 55 GPa, the effect is good, and it can also be greater than 35 GPa and less than 50 GPa. Thus, the coating 3 has sufficient hardness. The hardness of the entire coating 3 is measured by a nano indenter method (Nano Indenter XP manufactured by MTS). Specifically, by the method according to ISO14577, the measurement load is set to 10 mN (1 gf), and the hardness of three parts on the surface of the coating 3 is measured, and the average value of the hardness of the three parts is calculated. This average value is equivalent to the hardness of the coating 3.
[0143] <First Floor>
[0144] The first layer 13 of the present embodiment is composed of alternating layers in which the first unit layers 12 and the second unit layers 15 are alternately stacked. The first layer 13 is composed of alternating layers in which the first unit layers 12 and the second unit layers 15 are alternately stacked, which means that a thin film sample including a cross section of the coating 3 can be observed using a TEM (transmission electron microscope) and confirmed by a contrast difference.
[0145] Either the first unit layer 12 or the second unit layer 15 may be arranged at a position closest to the substrate 2. Figure 1 In the embodiment, a first unit layer 12 is arranged just above the substrate 2. Figure 2 In the embodiment, the second unit layer 15 is arranged just above the substrate 2. Either the first unit layer 12 or the second unit layer 15 may be arranged on the surface side of the coating 3. Figure 1 In the embodiment, the second unit layer 15 is arranged on the surface side of the coating 3. Figure 2 In the embodiment, the first unit layer 12 is arranged on the surface side of the coating 3 .
[0146] The thickness of the first layer 13 may be 0.5 μm or more and 15 μm or less. If the thickness of the first layer 13 is 0.5 μm or more, excellent wear resistance can be exhibited in continuous processing. If the thickness of the first layer 13 is 15 μm or less, excellent chipping resistance can be exhibited in intermittent cutting.
[0147] The thickness of the first layer 13 is measured by observing and measuring the cross section of the coating 3 using a transmission electron microscope (TEM). The specific measurement method is as follows. Cut the cutting tool 1 in the direction along the normal line of the surface of the coating 3 to prepare a thin slice sample including the cross section of the coating 3. Observe the thin slice sample with a TEM. The observation magnification is set to 20,000 to 5,000,000 times, and the measurement field of view is set to 0.0016 to 80 μm. 2 In one field of view, the thickness widths of three locations of the first layer 13 are measured, and the average value of the thickness widths of the three locations is calculated. The average value corresponds to the thickness of the first layer 13 .
[0148] The first unit layer 12 may have a hexagonal crystal structure. The hexagonal crystal structure is derived from W (C 1-a N a ) x The fact that the first unit layer 12 has a hexagonal crystal structure can be confirmed by analyzing the XRD measurement. In the obtained XRD spectrum, ε-W2C (01-076-7103) and W2C (01-076-7103) belonging to JCPDS (ICDD) were observed. 4.6 In the case of the peak of the hexagonal crystal defined in N4 (01-077-2001), it was confirmed that the first unit layer 12 had a hexagonal crystal structure.
[0149] When the coating includes the first unit layer and also includes other layers such as the second unit layer 15, the second layer 16, the third layer 14, the intermediate layer, and when peaks originating from layers other than the first unit layer 12 and the substrate are detected in the XRD spectrum from the surface of the coating 3 (hereinafter also referred to as "other peaks"), it can also be identified that the first unit layer 12 has a hexagonal crystal structure.
[0150] An example of an apparatus used for X-ray diffraction measurement is "SmartLab" (trade name) manufactured by Rigaku Co., Ltd. The conditions for XRD measurement are as follows.
[0151] (XRD measurement conditions)
[0152] Scanning axis: 2θ-θ
[0153] X-ray source: Cu-Kα ray
[0154] Detector: 0-dimensional detector (scintillation counter)
[0155] Tube voltage: 45kV
[0156] Tube current: 40mA
[0157] Incident optical system: using mirror
[0158] Light receiving optical system: Using analyzer crystal (PW3098 / 27)
[0159] Step length: 0.03°
[0160] Cumulative time: 2 seconds
[0161] Scanning range (2θ): 10°~120°
[0162] <Composition of the First Unit Layer and Composition of the Second Unit Layer>
[0163] The first unit layer 12 is composed of W(C1-a N a ) x In the configuration, a is 0.3 to 0.8, and x is 0.8 to 1.2. Thus, the crystal structure of the first cell layer 12 becomes a hexagonal crystal, and the heat resistance, oxidation resistance, and wear resistance of the first cell layer 12 can be improved.
[0164] The lower limit of a is 0.3 or more, 0.35 or more, 0.40 or more, or 0.45 or more. The upper limit of a is 0.8 or less, 0.75 or less, 0.70 or less, or 0.65 or less. a can be 0.35 or more and 0.75 or more, 0.40 or more and 0.70 or less, or 0.45 or more and 0.65 or less.
[0165] The lower limit of x is 0.8 or more, 0.85 or more, or 0.90 or more. The upper limit of x is 1.2 or less, 1.15 or less, or 1.10 or less. x may be 0.85 or more and 1.15 or less, 0.90 or more and 1.10 or less, or 1.00.
[0166] In this disclosure, “the first unit layer is composed of W(C 1-a N a ) x "Constituted" means that as long as the effect of the present disclosure is not impaired, the first unit layer 12 can be in W(C 1-a N a ) x In addition, it also includes inevitable impurities. Examples of inevitable impurities include oxygen and carbon. The overall content of inevitable impurities in the first unit layer 12 may be greater than 0 atomic % and less than 1 atomic %. In the present disclosure, "atomic %" refers to the ratio (%) of the number of atoms to the total number of atoms constituting the layer.
[0167] The second unit layer 15 is made of Al c V 1-c N composition, c is greater than 0.40 and less than 0.80. The second unit layer 15 can improve the heat resistance, oxidation resistance and toughness of the coating 3. The lower limit of c is greater than 0.40, and it can also be greater than 0.45, greater than 0.50, or greater than 0.55. The upper limit of c is less than 0.80, and it can also be less than 0.75, and it can also be less than 0.70, and it can also be less than 0.65. c can be greater than 0.45 and less than 0.75, and it can also be greater than 0.50 and less than 0.70, and it can also be greater than 0.55 and less than 0.65.
[0168] In this disclosure, “the second unit layer is composed of Al c V1-c N composition" means that the second unit layer 15 may contain Al c V 1-c In addition to N, inevitable impurities are also included. Examples of the inevitable impurities include oxygen and carbon. The total content of the inevitable impurities in the second unit layer 15 may be greater than 0 atomic % and less than 1 atomic %.
[0169] The above-mentioned a, the above-mentioned x, the above-mentioned c and the content of inevitable impurities in the first unit layer 12 and the content of inevitable impurities in the second unit layer 15 are measured by performing elemental analysis on the cross section of the coating 3 using a transmission electron microscope (TEM). The specific measurement method is as follows. Cut the cutting tool 1 in the direction along the normal line of the surface of the coating 3 to prepare a thin slice sample containing the cross section of the coating 3. Use EDS (Energy Dispersive X-ray Spectroscopy) attached to the TEM to irradiate the thin slice sample with an electron beam, measure the energy and the number of times the characteristic X-rays generated at this time, and perform elemental analysis on the first unit layer 12 and the second unit layer 15. Five layers are randomly selected from the first unit layer 12 and the second unit layer 15, respectively, and elemental analysis is performed. The average composition of the five layers of the first unit layer 12 is calculated. The average composition is equivalent to the composition of the first unit layer 12. The average composition of the five layers of the second unit layer 15 is calculated. The average composition is equivalent to the composition of the second unit layer 15. When the number of layers of the first unit layer 12 and the second unit layer 15 is four or less, elemental analysis is performed on all the layers to find the average composition of the first unit layer 12 and the second unit layer 15. It was confirmed that as long as the measurement is performed in the same cutting tool 1, there is no deviation in the measurement result even if the measurement position is arbitrarily selected.
[0170] In the present disclosure, the composition W(C 1-a N a ) x The total number of C and N atoms is A N1 Atomic number A relative to W M1 Ratio A N1 / A M1 is greater than or equal to 0.8 and less than or equal to 1.2. In the present disclosure, the composition Al of the second unit layer c V 1-c In N, the number of atoms of N is A N2 Relative to the total number of atoms of Al and V A M2 Ratio A N2 / A M2 In manufacturing, it must be greater than 0.8 and less than 1.2. N1 / A M1 And than AN2 / A M2 It can be measured by Rutherford backscattering (RBS) method. N1 / A M1 And than A N2 / A M2 It can be confirmed that the effect of the present disclosure is not impaired within the above range.
[0171] <Average Thickness of the First Unit Layer and Average Thickness of the Second Unit Layer>
[0172] The average thickness of the first unit layer 12 may be greater than or equal to 0.002 μm and less than or equal to 0.2 μm, and the average thickness of the second unit layer 15 may be greater than or equal to 0.002 μm and less than or equal to 0.2 μm. Thus, the progress of cracks generated on the surface of the coating 3 can be further suppressed. The lower limit of the average thickness of the first unit layer 12 may be greater than or equal to 0.002 μm, or may be greater than or equal to 0.005 μm, or may be greater than or equal to 0.01 μm. The upper limit of the average thickness of the first unit layer 12 may be less than or equal to 0.20 μm, or may be less than or equal to 0.15 μm, or may be greater than or equal to 0.10 μm. The average thickness of the first unit layer 12 may be greater than or equal to 0.005 μm and less than or equal to 0.15 μm, or may be greater than or equal to 0.01 μm and less than or equal to 0.1 μm. The lower limit of the average thickness of the second unit layer 15 may be greater than or equal to 0.002 μm, or may be greater than or equal to 0.005 μm, or may be greater than or equal to 0.01 μm. The upper limit of the average thickness of the second cell layer 15 may be 0.20 μm or less, 0.15 μm or less, or 0.10 μm or less. The average thickness of the second cell layer 15 may be 0.005 μm to 0.15 μm or 0.01 μm to 0.10 μm or less.
[0173] The average thickness of the first unit layer 12 and the average thickness of the second unit layer 15 can be measured by the same method as the above-mentioned method for measuring the thickness of the first layer 13 .
[0174] like Figure 5As shown, in the first unit layer 12 and the second unit layer 15 adjacent to the first unit layer 12, the ratio λ2 / λ1 of the thickness λ2μm of the second unit layer 15 to the thickness λ1μm of the first unit layer 12 can be greater than 1.0 and less than 5.0. The second unit layer 15 has a low thermal conductivity and is difficult to transfer the heat generated during cutting to the substrate 2 on the basis of high oxidation resistance. If the ratio λ2 / λ1 is greater than 1.0, the proportion of the second unit layer 15 in the coating 3 is relatively increased, and the amount of Al in the coating 3 is increased, thereby improving the thermal blocking property of the cutting tool 1 as a whole. The wear resistance of the cutting tool 1 having the coating 3 is improved, especially during continuous cutting. If λ2 / λ1 is greater than 1.0, there is a tendency for the toughness of the coating 3 to increase. On the other hand, if λ2 / λ1 is less than 5.0, there is a tendency to easily obtain the effect of suppressing the progress of cracks brought about by laminating the first unit layer 12 and the second unit layer 15.
[0175] λ2 / λ1 can be greater than 1.0, greater than 1.1, greater than 1.2, greater than 1.3, greater than 1.4, greater than 1.5, greater than 2.0, or greater than 2.5. λ2 / λ1 can be less than 5.0, less than 4.0, or less than 3.0. λ2 / λ1 can be greater than 1.2 and less than 4.0, or greater than 1.5 and less than 2.5. Figure 5 In the figure, for the sake of explanation, the thicknesses of the three first unit layers 12 are all represented as λ1, and the thicknesses of the three second unit layers 15 are all represented as λ2. However, as long as the above-mentioned λ2 / λ1 relationship is satisfied between the adjacent first unit layers and second unit layers, the thicknesses λ1 of the three first unit layers 12 do not need to be the same, and the thicknesses λ2 of the three second unit layers 15 do not need to be the same.
[0176] In the first layer 13, the stacking number of the first unit layer 12 and the second unit layer 15 can be 5 or more and 500 or less, or 10 or more and 500 or less. Thus, by stacking the first unit layer 12 and the second unit layer 15, the effect of improving the hardness and the compressive residual stress in a balanced manner can be fully obtained. In the first layer 13, the stacking number of the first unit layer 12 and the second unit layer 15 can be 100 or more and 400 or less, or 200 or more and 350 or less.
[0177] The stacking numbers of the first unit layers 12 and the second unit layers 15 in the first layer 13 can be determined by observing a thin sample of a cross section of the coating 3 using a TEM (transmission electron microscope) at a TEM observation magnification of 20,000 to 5,000,000.
[0178] <Second Floor>
[0179] like Figure 3 as well as Figure 4 As shown, the coating 3 further includes a second layer 16 disposed between the substrate 2 and the first layer 13. The composition of the second layer 16 may be the same as that of the first unit layer 12 or the second unit layer 15. Thus, the adhesion between the substrate 2 and the coating 3 can be improved.
[0180] When the composition of the second layer 16 is the same as that of the first unit layer 12 , even when the second layer 16 is exposed at the initial stage of cutting, the sliding property of the second layer 16 is good, and thus the wear resistance can be improved.
[0181] When the composition of the second layer 16 is the same as that of the first unit layer 12, the thickness of the second layer 16 may be thicker than that of the first unit layer 12. Thus, the close contact between the substrate 2 and the coating 3 can be further improved. In addition, even when the second layer 16 is exposed at the initial stage of cutting, the sliding characteristics of the second layer 16 are good, so the wear resistance can be improved. "The thickness of the second layer is thicker than the thickness of the first unit layer" can be translated as "the thickness of the second layer exceeds 1.0 times the thickness of the first unit layer". The thickness of the second layer 16 may be 2.0 times or more, 4.0 times or more, or 10.0 times or more of the thickness of the first unit layer 12. The thickness of the second layer 16 may be 500 times or less, 120 times or less, or 50 times or less of the thickness of the first unit layer 12. The thickness of the second layer 16 may be 2.0 times or more and 500 times or more, 4.0 times or more and 120 times or less, or 10.0 times or more and 50 times or less of the thickness of the first unit layer 12.
[0182] When the composition of the second layer 16 is the same as that of the first unit layer 12, the thickness of the second layer 16 can be 0.1 μm or more. If the thickness of the second layer 16 is less than 0.1 μm, it is difficult to obtain the effect of improving wear resistance by setting the second layer 16 to the same composition as the first unit layer 12. When the composition of the second layer 16 is the same as that of the first unit layer 12, the thickness of the second layer 16 can be 0.3 μm or more, or 0.4 μm or more. The upper limit of the thickness of the second layer 16 is not particularly limited. If it exceeds 2 μm, the grains are enlarged and grain boundaries are generated, so there is a tendency to be difficult to obtain the effect of improving wear resistance. Therefore, considering the cost aspect, the thickness of the second layer 16 can be set to 2 μm or less.
[0183] In the case where the composition of the second layer 16 is the same as that of the first unit layer 12, as Figure 3 As shown, the first unit layer 12 may also be stacked just above the second layer 16. Figure 4As shown, the second unit layer 15 may be stacked just above the second layer 16. When the composition of the second layer 16 is the same as that of the first unit layer 12 and the first unit layer 12 is stacked just above the second layer 16, the second layer 16 and the first unit layer 12 have a continuous crystal structure.
[0184] When the composition of the second layer 16 is the same as that of the second unit layer 15, the thickness of the second layer 16 may be thicker than that of the second unit layer 15. Thus, the close contact between the substrate 2 and the coating 3 can be further improved. In addition, even if the second layer 16 is exposed at the initial stage of cutting, oxidation from the interface between the substrate 2 and the coating 3 can be suppressed, and cutting heat can be blocked. "The thickness of the second layer is thicker than the thickness of the second unit layer" can be translated as "the thickness of the second layer exceeds 1.0 times the thickness of the second unit layer". The thickness of the second layer 16 may be 2.0 times or more, 4.0 times or more, or 10.0 times or more of the thickness of the second unit layer 15. The thickness of the second layer 16 may be 500 times or less, 120 times or less, or 50 times or less of the thickness of the second unit layer 15. The thickness of the second layer 16 may be 2.0 times or more and 500 times or more, 4.0 times or more and 120 times or less, or 10.0 times or more and 50 times or less of the thickness of the second unit layer 15.
[0185] When the composition of the second layer 16 is the same as that of the second unit layer 15, the thickness of the second layer 16 can be 0.1 μm or more. If the thickness of the second layer 16 is less than 0.1 μm, it is difficult to obtain the effect of suppressing oxidation from the interface between the substrate 2 and the coating 3 and the effect of blocking cutting heat by setting the second layer 16 to the same composition as the second unit layer 15. When the composition of the second layer 16 is the same as that of the second unit layer 15, the thickness of the second layer 16 can be 0.3 μm or more, or 0.4 μm or more. The upper limit of the thickness of the second layer 16 is not particularly limited. If it exceeds 2 μm, the grains are enlarged and grain boundaries are generated, which makes it difficult to further improve the above-mentioned oxidation suppression effect. Therefore, considering the cost aspect, the thickness of the second layer 16 can be set to 2 μm or less.
[0186] In the case where the composition of the second layer 16 is the same as that of the second unit layer 15, as Figure 3 As shown, the first unit layer 12 may also be stacked just above the second layer 16. Figure 4 As shown, the second unit layer 15 may be stacked just above the second layer 16. When the composition of the second layer 16 is the same as that of the second unit layer 15, and when the second unit layer 15 is stacked just above the second layer 16, the second layer 16 and the second unit layer 15 have a continuous crystal structure.
[0187] <Third Floor>
[0188] like Figure 1 to Figure 4 As shown, the coating 3 further includes a third layer 14 provided on the opposite side of the first layer 13 from the substrate 2, and the third layer 14 may be made of AlVCN. This can reduce the friction coefficient of the coating 3 and extend the life of the cutting tool 1.
[0189] Generally speaking, carbonitrides tend to have a lower friction coefficient with respect to the cut material than nitrides. It is believed that such a reduction in the friction coefficient is due to the contribution of carbon atoms. If the coating 3 includes the third layer 14, the friction coefficient of the coating 3 with respect to the cut material is reduced, and the life of the cutting tool 1 is prolonged.
[0190] The third layer 14 can be given a predetermined color by adjusting the composition ratio of N and C. This can impart design and recognition properties to the appearance of the cutting tool 1, which is commercially useful.
[0191] The thickness of the third layer 14 may be 0.1 μm or more. If the thickness of the third layer 14 is 0.1 μm or more, the effect of imparting lubricity by the third layer 14 is easily obtained. On the other hand, the upper limit of the thickness of the third layer 14 is not particularly limited, but if it exceeds 2 μm, there is a tendency that the effect of imparting lubricity described above cannot be further improved. Therefore, considering the cost aspect, the thickness of the third layer 14 may be 2 μm or less.
[0192] <Middle Layer>
[0193] The coating 3 may include an intermediate layer disposed between the second layer 16 and the first layer 13, or between the first layer 13 and the third layer 14. Examples of the intermediate layer include AlVCeN, AlVN, AlVBN, AlVSiN, AlVYN, and AlVLaN. The thickness of the intermediate layer may be 0.1 μm to 2 μm, 0.3 μm to 1.5 μm, or 0.4 μm to 1.0 μm.
[0194] [Second embodiment: cutting tool (2)]
[0195] use Figure 6 to Figure 10 A cutting tool according to another embodiment of the present disclosure will be described.
[0196] A cutting tool 1 according to another embodiment of the present disclosure (hereinafter also referred to as a “second embodiment”) includes a substrate 2 and a coating 3 disposed on the substrate 2, wherein:
[0197] The coating 3 includes a 1A layer 13A,
[0198] The 1A layer 13A is composed of an alternating layer in which the first unit layer 12 and the third unit layer 17 are alternately stacked.
[0199] The first unit layer has a hexagonal crystal structure,
[0200] The first unit layer 12 is composed of W (C 1-a N a ) x constitute,
[0201] a is 0.3 or more and 0.8 or less,
[0202] x is 0.8 or more and 1.2 or less,
[0203] The third unit layer 17 is made of Al d V 1-d-e M e N constitutes,
[0204] M is silicon, boron, yttrium, cerium or lanthanum,
[0205] d is 0.40 or more and 0.80 or less,
[0206] e is greater than 0 and less than or equal to 0.05.
[0207] The cutting tool 1 of the first embodiment can have a long tool life even in cutting processing performed under the condition of high cutting edge temperature. The reason for this is presumably as follows.
[0208] The first unit layer 12 is composed of W (C 1-a N a ) x The first unit layer 12 contains C (carbon), so the friction coefficient at the contact interface with the cut material is reduced, which can reduce the cutting resistance. 1-a N a ) x Since N (nitrogen) is contained, the heat resistance is improved by about 150°C compared to WC. As a result, the first layer including the first unit layer can improve the wear resistance in processing where the cutting edge becomes high temperature during dry cutting, etc. Therefore, the tool life of the cutting tool including the first layer is improved.
[0209] When comparing a layer composed of a nitride of Al and V (hereinafter also referred to as an "AlVN layer") with a layer composed of a nitride containing Al, V and M (M is silicon, boron, yttrium, cerium or lanthanum) (hereinafter also referred to as an "AlVMN layer"), the AlVMN layer is less likely to undergo spinodal decomposition of AlVN at high temperatures. If spinodal decomposition occurs, soft hexagonal AlN precipitates and hardness decreases. The AlVMN layer can suppress hardness decrease even at high temperatures and has the characteristics of large compressive residual stress and excellent crack resistance. The AlVMN layer has the characteristic of high thermal blocking properties. The 1A layer 13A is composed of W (C 1-a N a ) x The first unit layer 12 and the third unit layer 17 composed of the AlVMN layer are alternately stacked in an alternating layer structure, so it is possible to have the characteristics of high hardness and low friction coefficient of the first unit layer 12 and the characteristics of high thermal blocking properties of the third unit layer 17. The large compressive residual stress of the third unit layer 17 is supplemented by the small compressive residual stress of the first unit layer 12. Therefore, as the 1A layer 13A as a whole, the hardness, thermal blocking properties and compressive residual stress are improved in a balanced manner, and the life of the cutting tool 1 including the 1A layer 13A becomes longer.
[0210] The third unit layer 17 is oxidized during cutting to generate V2O5, which is an oxide of V. V2O5 has a melting point of 690°C, so it softens at the temperature during cutting and functions as a lubricant, which can reduce the friction coefficient on the tool rake face.
[0211] The 1A layer 13A is composed of alternating layers in which the first unit layer 12 and the third unit layer 17 are alternately stacked. The composition and lattice are discontinuous at the interface between the first unit layer 12 and the third unit layer 17. Therefore, when cracks are generated from the surface of the coating 3 during cutting, the progress of the cracks can be suppressed at the interface. Therefore, chipping and defection are suppressed, and the life of the cutting tool 1 is further extended.
[0212] The cutting tool 1 of the second embodiment can be basically configured similarly to the cutting tool 1 of the first embodiment except for the configurations of the 1A layer 13A, the 2A layer 16, and the 3A layer 14A. The "1A layer", "2A layer", and "3A layer" will be described below.
[0213] <1A Floor>
[0214] The 1A layer 13A of the present embodiment is composed of alternating layers in which the first unit layer 12 and the third unit layer 17 are alternately stacked. The fact that the 1A layer 13A is composed of alternating layers in which the first unit layer 12 and the third unit layer 17 are alternately stacked can be confirmed by observing the cross section of the coating 3 using a TEM (transmission electron microscope) and by the contrast difference. The thickness of the 1A layer 13A can be the same as the thickness of the first layer 13 described in the first embodiment.
[0215] <Composition of the First Unit Layer and Composition of the Third Unit Layer>
[0216] The composition W (C) of the first unit layer 12 of the second embodiment is 1-a N a ) x The composition W(C) of the first unit layer 12 of the first embodiment may be 1-a N a ) x same.
[0217] The third unit layer 17 is made of Al d V 1-d-e M e N, M is silicon, boron, yttrium, cerium or lanthanum, d is 0.40 to 0.80, and e is greater than 0 to 0.05. The third unit layer 17 can have both excellent hardness and excellent oxidation resistance. The reason is presumably as follows.
[0218] When M is silicon, the structure of the third cell layer 17 becomes finer, thereby improving the hardness and oxidation resistance of the third cell layer 17 and improving the hardness and oxidation resistance of the entire film 3 .
[0219] When M is boron, the hardness of the third unit layer 17 increases due to boron, and the hardness of the entire coating 3 increases. In addition, the boron oxide formed by oxidation of the surface of the cutting tool 1 accompanying cutting densifies the Al oxide in the third unit layer 17, thereby improving the oxidation resistance of the third unit layer 17. In addition, since the boron oxide has a low melting point, it acts as a lubricant during cutting and can suppress the adhesion of the cut material.
[0220] When M is yttrium (Y), cerium (Ce) or lanthanum (La), the lattice constant of YN is The lattice constant of CeN is The lattice constant of LaN is The lattice constants of YN, CeN and LaN are greater than that of TiN And the lattice constant of AlN Therefore, in the case of a cubic Al d V1-d-e M e Strain is introduced into the third unit layer 17 composed of N, and the structure is refined, so that the hardness and wear resistance of the third unit layer 17 are improved, and the life of the cutting tool 1 including the third unit layer 17 is further extended.
[0221] The above-mentioned d is greater than or equal to 0.40 and less than or equal to 0.80. As a result, the crystal structure of the third unit layer 17 becomes a cubic crystal, the third unit layer 17 has a high hardness, and the wear resistance is improved. The lower limit of d can be greater than or equal to 0.45, or greater than or equal to 0.50, or greater than or equal to 0.55. The upper limit of d can be less than or equal to 0.75, or less than or equal to 0.70, or less than or equal to 0.65. d can be greater than or equal to 0.45 and less than or equal to 0.75, or greater than or equal to 0.50 and less than or equal to 0.70, or greater than or equal to 0.55 and less than or equal to 0.65.
[0222] The above-mentioned e is greater than 0 and less than 0.05. Thus, the hardness and oxidation resistance of the 1A layer 13A can be improved. The lower limit of e can be greater than 0.002, or greater than 0.005, or greater than 0.01, or greater than 0.02. The e can be less than 0.04, or less than 0.03. e can be greater than 0.002 and less than 0.05, or greater than 0.01 and less than 0.05, or greater than 0.01 and less than 0.03, or greater than 0.02 and less than 0.03.
[0223] In this disclosure, “the third unit layer is composed of Al d V 1-d-e M e N composition" means that the third unit layer 17 may contain Al d V 1-d-e M e In addition to N, inevitable impurities are also included. Examples of the inevitable impurities include oxygen and carbon. The total content of the inevitable impurities in the third unit layer 17 may be greater than 0 atomic % and less than 1 atomic %.
[0224] The contents of d, e and the inevitable impurities of the third unit layer 17 are determined by the same method as the measurement method of a. It is confirmed that if the measurement is performed using the same cutting tool 1, there is no variation in the measurement results even if the measurement site is arbitrarily selected.
[0225] In the present disclosure, the composition W(C 1-a N a ) x The total number of C and N atoms is A N1 Atomic number A relative to WM1 Ratio A N1 / A M1 is greater than or equal to 0.8 and less than or equal to 1.2. In the present disclosure, the composition Al of the third unit layer d V 1-d- e M e In N, the number of atoms of N is A N3 A relative to the total number of atoms of Al, V and M M3 Ratio A N3 / A M3 In manufacturing, it must be greater than 0.8 and less than 1.2. N1 / A M1 And than A N3 / A M3 It can be measured by Rutherford backscattering (RBS) method. N1 / A M1 And than A N3 / A M3 It can be confirmed that the effect of the present disclosure is not impaired within the above range.
[0226] <Average Thickness of the First Unit Layer and Average Thickness of the Third Unit Layer>
[0227] The average thickness of the first unit layer 12 may be greater than or equal to 0.002 μm and less than or equal to 0.2 μm, and the average thickness of the third unit layer 17 may be greater than or equal to 0.002 μm and less than or equal to 0.2 μm. Thus, the progress of cracks generated on the surface of the coating 3 can be further suppressed. The lower limit of the average thickness of the first unit layer 12 may be greater than or equal to 0.002 μm, or may be greater than or equal to 0.005 μm, or may be greater than or equal to 0.01 μm. The upper limit of the average thickness of the first unit layer 12 may be less than or equal to 0.20 μm, or may be less than or equal to 0.15 μm, or may be less than or equal to 0.10 μm. The average thickness of the first unit layer 12 may be greater than or equal to 0.005 μm and less than or equal to 0.15 μm, or may be greater than or equal to 0.01 μm and less than or equal to 0.1 μm. The lower limit of the average thickness of the third unit layer 17 may be greater than or equal to 0.002 μm, or may be greater than or equal to 0.005 μm, or may be greater than or equal to 0.01 μm. The upper limit of the average thickness of the third cell layer 17 may be 0.20 μm or less, 0.15 μm or less, or 0.10 μm or less. The average thickness of the third cell layer 17 may be 0.005 μm to 0.15 μm, or 0.01 μm to 0.10 μm or less.
[0228] The average thickness of the first unit layer 12 and the average thickness of the third unit layer 17 can be determined by the same method as the method for measuring the thickness of the first layer 13 described above.
[0229] like Fig.10 As shown, in the first unit layer 12 and the third unit layer 17 adjacent to the first unit layer 12, the ratio λ3 / λ1 of the thickness λ3 of the third unit layer 17 to the thickness λ1 of the first unit layer 12 can be greater than 1.0 and less than 5.0. The third unit layer 17 has a low thermal conductivity and is difficult to transfer the heat generated during cutting to the substrate 2 on the basis of high oxidation resistance. If the ratio λ3 / λ1 is greater than 1.0, the proportion of the third unit layer 17 in the coating 3 is relatively increased, and the amount of Al in the coating 3 is increased, thereby improving the thermal blocking property of the cutting tool 1 as a whole. The cutting tool 1 having the coating 3 has improved wear resistance, especially during continuous cutting. If λ3 / λ1 is greater than 1.0, there is a tendency that the toughness of the coating 3 is improved. On the other hand, if λ3 / λ1 is less than 5.0, there is a tendency that the effect of suppressing crack progression brought about by laminating the first unit layer 12 and the third unit layer 17 is easily obtained.
[0230] λ3 / λ1 may be greater than 1.0, greater than 1.1, greater than 1.2, greater than 1.3, greater than 1.4, greater than 1.5, or greater than 2.0. λ3 / λ1 may be less than 5.0, less than 4.0, or less than 3.0. λ3 / λ1 may be greater than 1.0 and less than 5.0, greater than 1.2 and less than 4.0, greater than 1.5 and less than 4.0, greater than 1.0 and less than 3.0, or greater than 2.0 and less than 3.0. Fig.10 In the figure, for the sake of explanation, the thicknesses of the three first unit layers 12 are all represented as λ1, and the thicknesses of the three third unit layers 17 are all represented as λ3. However, as long as the above-mentioned λ3 / λ1 relationship is satisfied between the adjacent first unit layers and third unit layers, the thicknesses λ1 of the three first unit layers 12 do not need to be the same, and the thicknesses λ3 of the three third unit layers 17 do not need to be the same.
[0231] In the 1A layer 13A, the stacking number of the first unit layer 12 and the third unit layer 17 can be 4 or more and 800 or less, or 10 or more and 500 or less. Thus, by stacking the first unit layer 12 and the third unit layer 17, there is a tendency to easily obtain the effect of improving the hardness and the compressive residual stress in a balanced manner. In the 1A layer 13A, the stacking number of the first unit layer 12 and the third unit layer 17 can be 100 or more and 400 or less, or 200 or more and 350 or less.
[0232] In the 1A layer 13A, the stacking numbers of the first unit layers 12 and the third unit layers 17 can be determined by the same method as the method for measuring the stacking numbers of the first unit layers 12 and the second unit layers 15 described in the first embodiment.
[0233] <2A Floor>
[0234] like Figure 8 as well as Fig. 9 As shown, the coating 3 further includes a 2A layer 16A disposed between the substrate 2 and the 1A layer 13A, and the composition of the 2A layer 16A may be the same as the composition of the first unit layer 12 or the composition of the third unit layer 17. Thus, the adhesion between the substrate 2 and the coating 3 can be improved.
[0235] When the composition of the 2A layer 16A is the same as that of the first unit layer 12 , even when the 2A layer 16A is exposed at the initial stage of cutting, the sliding property of the 2A layer 16A is good, and thus the wear resistance can be improved.
[0236] When the composition of the 2A layer 16A is the same as that of the first unit layer 12, the thickness of the 2A layer 16A may be thicker than the thickness of the first unit layer 12. Thus, the close contact between the substrate 2 and the coating 3 can be further improved. In addition, even when the 2A layer 16A is exposed at the beginning of cutting, the sliding characteristics of the 2A layer 16A are good, so the wear resistance can be improved. "The thickness of the 2A layer is thicker than the thickness of the first unit layer" can be translated as "the thickness of the 2A layer exceeds 1.0 times the thickness of the first unit layer". The thickness of the 2A layer 16A may be more than 2.0 times the thickness of the first unit layer 12, or more than 4.0 times, or more than 10.0 times. The thickness of the 2A layer 16A may be less than 500 times the thickness of the first unit layer 12, or less than 120 times, or less than 50 times. The thickness of the 2A layer 16A may be 2.0 times or more and 500 times or less, 4.0 times or more and 120 times or less, or 10.0 times or more and 50 times or less the thickness of the first unit layer 12 .
[0237] When the composition of the 2A layer 16A is the same as that of the first unit layer 12, the thickness of the 2A layer 16A can be 0.1 μm or more. If the thickness of the 2A layer 16A is less than 0.1 μm, there is a tendency that it is difficult to obtain the effect of improving wear resistance by setting the 2A layer 16A to the same composition as the first unit layer 12. When the composition of the 2A layer 16A is the same as that of the first unit layer 12, the thickness of the 2A layer 16A can be 0.3 μm or more, or 0.4 μm or more. The upper limit of the thickness of the 2A layer 16A is not particularly limited. If it exceeds 2 μm, the grains are enlarged and grain boundaries are generated, so there is a tendency that it is difficult to obtain the effect of improving wear resistance. Therefore, considering the cost aspect, the thickness of the 2A layer 16A can be set to 2 μm or less.
[0238] In the case where the composition of the 2A layer 16A is the same as that of the first unit layer 12, Figure 8 As shown in FIG. 1 , the first unit layer 12 may be stacked just above the 2A layer 16A. Fig. 9 As shown, the second unit layer 15 may be stacked just above the 2A layer 16A. When the composition of the 2A layer 16A is the same as that of the first unit layer 12, and the first unit layer 12 is stacked just above the 2A layer 16A, the 2A layer 16A and the first unit layer 12 have a continuous crystal structure.
[0239] When the composition of the 2A layer 16A is the same as that of the third unit layer 17, the third unit layer 17 tends to have a small stress, so the peeling resistance of the coating 3 can be improved, especially in intermittent processing such as milling and end milling where loads are repeatedly applied to the tool tip.
[0240] When the composition of the 2A layer 16A is the same as that of the third unit layer 17, the thickness of the 2A layer 16A may be thicker than the thickness of the third unit layer 17. Thus, the adhesion between the substrate 2 and the coating 3 can be further improved. In addition, even if the 2A layer 16A is exposed at the initial stage of cutting, oxidation from the interface between the substrate 2 and the coating 3 can be suppressed, and cutting heat can be blocked. "The thickness of the 2A layer is thicker than the thickness of the third unit layer" can be translated as "the thickness of the 2A layer exceeds 1.0 times the thickness of the third unit layer". The thickness of the 2A layer 16A may be more than 2.0 times the thickness of the third unit layer 17, or more than 4.0 times, or more than 10.0 times. The thickness of the 2A layer 16A may be less than 500 times the thickness of the third unit layer 17, or less than 120 times, or less than 50 times. The thickness of the 2A layer 16A may be 2.0 to 500 times, 4.0 to 120 times, or 10.0 to 50 times the thickness of the third unit layer 17 .
[0241] When the composition of the 2A layer 16A is the same as that of the third unit layer 17, the thickness of the 2A layer 16A may be 0.1 μm or more. If the thickness of the 2A layer 16A is less than 0.1 μm, it is difficult to obtain the effect of suppressing oxidation from the interface between the substrate 2 and the coating 3 and the effect of blocking cutting heat by setting the 2A layer 16A to the same composition as the third unit layer 17. When the composition of the 2A layer 16A is the same as that of the third unit layer 17, the thickness of the 2A layer 16A may be 0.3 μm or more, or 0.4 μm or more. The upper limit of the thickness of the 2A layer 16A is not particularly limited. If it exceeds 2 μm, the grains are enlarged and grain boundaries are generated, and it is difficult to further improve the above-mentioned oxidation suppression effect. Therefore, considering the cost aspect, the thickness of the 2A layer 16A may be set to 2 μm or less.
[0242] In the case where the composition of the 2A layer 16A is the same as the composition of the third unit layer 17, Figure 8 As shown in FIG. 1 , the first unit layer 12 may be stacked just above the 2A layer 16A. Fig. 9 As shown, the third unit layer 17 may be stacked just above the 2A layer 16A. When the composition of the 2A layer 16A is the same as that of the third unit layer 17, and when the third unit layer 17 is stacked just above the 2A layer 16A, the 2A layer 16A and the third unit layer 17 have a continuous crystal structure.
[0243] <3A Floor>
[0244] like Figure 6 to Figure 9 As shown, the coating 3 further includes a 3A layer 14A disposed on the opposite side of the first layer 13 from the substrate 2, and the 3A layer 14A can be composed of AlVMeCN. Among them, Me can be silicon, boron, yttrium, cerium or lanthanum. Me can be the same element as M used in the third unit layer. As a result, the friction coefficient of the coating 3 can be reduced, and the life of the cutting tool 1 can be extended.
[0245] Generally speaking, carbonitrides tend to have a lower friction coefficient with respect to the cut material than nitrides. It is believed that such a reduction in the friction coefficient is due to the contribution of carbon atoms. If the coating 3 includes the 3A layer 14A, the friction coefficient of the coating 3 with respect to the cut material is reduced, and the life of the cutting tool 1 is prolonged.
[0246] In the third A layer 14A, a predetermined color can be imparted by adjusting the composition ratio of N and C. This can impart design and recognition to the appearance of the cutting tool 1, which is commercially useful.
[0247] The thickness of the 3A layer 14A may be 0.1 μm or more. If the thickness of the 3A layer 14A is 0.1 μm or more, the lubricity imparting effect brought by the 3A layer 14A is easily obtained. On the other hand, the upper limit of the thickness of the 3A layer 14A is not particularly limited, but if it exceeds 2 μm, there is a tendency that the above-mentioned lubricity imparting effect cannot be further improved. Therefore, considering the cost aspect, the thickness of the 3A layer 14A may be 2 μm or less.
[0248] [Embodiment 3: Method for manufacturing cutting tool]
[0249] In Embodiment 3, a method for manufacturing the cutting tool 1 of the first embodiment or the second embodiment is described. The manufacturing method includes a first step of preparing a substrate 2 and a second step of forming a coating 3 on the substrate 2. The second step includes a step of forming the first layer 13 or the 1A layer 13A. The details of each step are described below.
[0250] <First Step>
[0251] In the first step, a substrate 2 is prepared. As the substrate 2, the substrate 2 described in the first embodiment can be used.
[0252] When cemented carbide is used as the substrate 2, a commercially available substrate can be used, or it can be manufactured by a general powder metallurgy method. When manufactured by a general powder metallurgy method, WC powder and Co powder are mixed by a ball mill or the like to obtain a mixed powder. After the mixed powder is dried, it is formed into a predetermined shape to obtain a formed body. By further sintering the formed body, a WC-Co based cemented carbide (sintered body) is obtained. Then, by subjecting the sintered body to predetermined tool tip processing such as honing, a substrate composed of a WC-Co based cemented carbide can be manufactured. Even a substrate other than the above, as long as it is a substrate previously known as such a substrate, can be prepared.
[0253] <Second step>
[0254] In the second step, the coating 3 is formed on the substrate 2. The second step includes a step of forming the first layer 13 or the 1A layer 13A.
[0255] In the "step of forming the first layer", the first layer 13 is formed by alternately stacking the first unit layer 12 and the second unit layer 15 using a physical vapor deposition (PVD) method. In the "step of forming the 1A layer", the first unit layer 12 and the third unit layer 17 are alternately stacked using a PVD method, thereby forming the 1A layer 13A. In order to improve the wear resistance of the coating 3 including the first layer 13 or the 1A layer 13A, it is effective to form a layer composed of a highly crystalline compound. The inventors of the present invention have studied various methods for forming the first layer 13 and the first layer 13A, and found that by using the physical vapor deposition method, a layer composed of a highly crystalline compound can be formed, and the coating 3 has excellent wear resistance.
[0256] As a PVD method, at least one selected from the group consisting of a cathode arc ion plating method, a balanced magnetron sputtering method, an unbalanced magnetron sputtering method, and a HiPIMS (High Power Impulse Magnetron Sputtering) method can be used. In particular, a cathode arc ion plating method with a high ionization rate of the raw material element can be used. When the cathode arc ion plating method is used, before forming the first layer 13 or the 1A layer 13A, the surface of the substrate 2 can be subjected to a metal ion bombardment treatment, so that the adhesion between the substrate 2 and the coating 3 including the first layer 13 or the 1A layer 13A is significantly improved.
[0257] Cathodic arc ion plating can be performed, for example, by placing a substrate 2 in an apparatus and a target as a cathode, applying a high voltage to the target to generate arc discharge, thereby ionizing and evaporating atoms constituting the target, and depositing a substance on the substrate 2 .
[0258] The balanced magnetron sputtering method can be carried out, for example, in the following manner: a substrate 2 is set in the device, and a target is set on a magnetron electrode having a magnet that forms a balanced magnetic field, high-frequency power is applied between the magnetron electrode and the substrate 2 to generate gas plasma, and gas ions generated by the generation of the gas plasma collide with the target, so that atoms released from the target are deposited on the substrate 2.
[0259] The unbalanced magnetron sputtering method can be performed by making the magnetic field generated by the magnetron electrodes in the above-mentioned balanced magnetron sputtering method unbalanced, for example. The HiPIMS method can also be used, which can obtain a dense film by applying a high voltage.
[0260] <Other Processes>
[0261] The second step may include a surface treatment step of coating such as grinding with a brush, dry or wet shot blasting, etc., on the basis of the step of forming the first layer 13 or the 1A layer 13A. In addition, the second step may include a step of forming other layers such as the second layer 16, the 2A layer 16A, the third layer 14, the 3A layer 14A, and the intermediate layer. The other layers can be formed by the conventionally known chemical vapor deposition method and the physical vapor deposition method. In a physical vapor deposition device, from the viewpoint of being able to form other layers continuously with the first unit layer 12, the second unit layer 15, or the third unit layer 17, the other layers are preferably formed by the physical vapor deposition method.
[0262] Example
[0263] The present embodiment will be described in more detail by way of examples, but the present embodiment is not limited to these examples.
[0264] [Example 1]
[0265] <Samples 1 to 25, Samples 101 to 106>
[0266] 《Manufacturing of cutting tools》
[0267] Fig.11 is a schematic cross-sectional view of the cathode arc ion plating device used in this embodiment, Fig.12 yes Fig.11 A schematic top view of the device.
[0268] exist Fig.11 as well as Fig.12 In the device, a cathode 106 for the first unit layer, a cathode 107 for the second unit layer, and a cathode 120 for the third layer, which are targets made of an alloy of metal raw materials for the coating 3, and a rotating substrate holder 104 for setting the substrate are installed in the chamber 101. The composition of the cathode 106 is adjusted so as to obtain the composition of the first unit layer in Table 1. The composition of the cathode 107 is adjusted so as to obtain the composition of the second unit layer in Table 1. The composition of the cathode 120 is adjusted so as to obtain the composition of the third layer in Table 2.
[0269] An arc power source 108 is mounted on the cathode 106, an arc power source 109 is mounted on the cathode 107, and an arc power source (not shown) is mounted on the cathode 120. In addition, a bias power source 110 is mounted on the substrate holder 104. In addition, a gas inlet 105 for introducing a gas 102 is provided in the chamber 101, and a gas exhaust port 103 is provided in order to adjust the pressure in the chamber 101, so that the gas 102 in the chamber 101 can be sucked from the gas exhaust port 103 by a vacuum pump.
[0270] On the substrate holder 104 , a chip having a base material of a cemented carbide grade of JIS standard P30 and a shape of CNMG120408 of JIS standard and a chip of SEMT13T3AGSN manufactured by Sumitomo Electric Hardmetal Co., Ltd. are mounted.
[0271] Next, the chamber 101 was depressurized by a vacuum pump, and the temperature was heated to 500° C. by a heater installed in the apparatus while the substrate was rotated, and the chamber 101 was evacuated until the pressure in the chamber 101 reached 1.0×10 -4 Then, argon gas was introduced from the gas inlet, the pressure in the chamber 101 was maintained at 2.0 Pa, the voltage of the bias power supply 110 was gradually increased to -1000 V, and the surface of the substrate was cleaned for 15 minutes. After that, the substrate was cleaned by exhausting argon gas from the chamber 101 (argon bombardment treatment). Through the above, the substrates of the cutting tools of each sample were prepared.
[0272] Next, while the substrate was rotated at the center, argon gas and nitrogen gas were introduced as reaction gases, and while the temperature of the substrate was maintained at 400°C, the reaction gas pressure was maintained at 3.0 Pa, and the voltage of the bias power supply 110 was maintained at a predetermined constant value in the range of -50V to -200V, an arc current of 100A was supplied to the cathode 106 and the cathode 107, respectively, thereby generating metal ions from the cathode 106 and the cathode 107, and forming the second layer having the composition shown in Table 2 and the first layer having the composition shown in Table 1 on the substrate. The purpose of introducing argon gas here is to form the first unit layer W (C 1-a N a ) x The surface of the WC cathode used in the case is cleaned. In the manufacturing method disclosed in the present invention, the temperature of the substrate is 400°C, which is lower than the existing nitride film formation temperature of 600°C. The reasons are as follows. The inventors of the present invention have found that when the temperature of the substrate is set to 600°C for film formation, there is a tendency for the hardness of the film to decrease. The reason for this has been studied, and it is speculated that this is because when the temperature of the substrate is set to 600°C for film formation, the carbon (C) contained in the cathode for the first unit layer becomes free carbon and precipitates in the formed film. As a result of in-depth research conducted by the inventors of the present invention, it was found that by setting the temperature of the substrate to 400°C for film formation, excellent hardness can be maintained even at high temperatures, forming a film with excellent wear resistance.
[0273] In the case where the second layer is formed, the first layer is formed by alternately stacking the first unit layer and the second unit layer on the second layer by the number of stacking layers shown in Table 1. In the case where the second layer is not formed, the first layer is formed by alternately stacking the first unit layer and the second unit layer on the substrate by the number of stacking layers shown in Table 1. In addition, the thickness of the second layer, the thickness of each of the first unit layer and the second unit layer in the first layer, and the number of stacking layers are adjusted by the rotation speed of the substrate. Then, when the thickness of the second layer and the first layer reaches the thickness shown in Table 1 and Table 2, respectively, the current supplied to the evaporation source is stopped.
[0274] Next, while introducing argon, nitrogen, and methane as reaction gases into the chamber 101, an arc current of 80A was supplied to the cathode 120 while maintaining the temperature of the substrate at 400°C, the reaction gas pressure at 2.0 Pa, and the voltage of the bias power supply 110 at -350V, thereby generating metal ions from the cathode 120 and forming the third layer on the first layer. When the thickness of the third layer reached the thickness shown in Table 2, the current supplied to the evaporation source was stopped. The amount of nitrogen gas introduced and the amount of methane gas introduced were adjusted so as to obtain the composition of the third layer in Table 2. In the above manner, cutting tools of various samples were produced.
[0275] Table 1
[0276]
[0277] Table 2
[0278]
[0279] "evaluate"
[0280] For the cutting tools involved in each sample, the composition of the first unit layer, the composition of the second unit layer, the composition of the second layer, the composition of the third layer, the number of stacking of the first unit layer and the second unit layer, the average thickness of the first unit layer, the average thickness of the second unit layer, the thickness of the first layer, the thickness of the second layer, the thickness of the third layer, λ2 / λ1 and the crystal structure of the first unit layer, and the hardness of the coating were measured.
[0281] <Measurement of Composition of First Unit Layer>
[0282] For each sample cutting tool, the composition of the first unit layer was measured by the method described in the first embodiment to obtain W (C 1-a N a The results are recorded in the "a" and "x" columns of Table 1. In Table 1, the case where "-" is recorded in the "a" column and the "x" column indicates that the first unit layer does not exist.
[0283] <Measurement of Composition of Second Unit Layer>
[0284] For the cutting tool of each sample, the composition of the second unit layer was measured by the method described in the first embodiment to obtain Al c V 1-c The value of c in N. The results are described in the column "c" of Table 1. In Table 1, the case where "-" is described in the column "c" means that the second unit layer does not exist.
[0285] <Measurement of Composition of Second Layer and Composition of Third Layer>
[0286] For each sample cutting tool, the composition of the second layer and the third layer was determined by the method described in the first embodiment. The results are recorded in the "Composition" column of the "Second Layer" and the "Composition" column of the "Third Layer" in Table 2. In the case where "-" is recorded in the "Composition" column of the "Second Layer" in Table 2, it means that the second layer does not exist, and in the case where "-" is recorded in the "Composition" column of the "Third Layer", it means that the third layer does not exist.
[0287] <Determination of the number of layers>
[0288] For each sample cutting tool, the stacking number of the first unit layer and the second unit layer was determined by the method described in the first embodiment. For example, a stacking number of 10 means that the alternating layer includes 10 first unit layers and 10 second unit layers. The obtained results are recorded in the "Stacking Number" column of Table 1.
[0289] <Measurement of Average Thickness of First Unit Layer, Average Thickness of Second Unit Layer, Thickness of First Layer, Thickness of Second Layer, and Thickness of Third Layer>
[0290] For the cutting tool of each sample, the average thickness of the first unit layer, the average thickness of the second unit layer, the thickness of the first layer, the thickness of the second layer, and the thickness of the third layer are determined by the method described in the first embodiment. The obtained results are recorded in the "Average Thickness [μm]" of "First Unit Layer", "Average Thickness [μm]" of "Second Unit Layer", "Thickness [μm]" of "First Layer" in Table 1, "Thickness [μm]" of "Second Layer", and "Thickness [μm]" of "Third Layer" in Table 2. The case where "-" is recorded in the "Thickness [μm]" column of "Second Layer" in Table 2 indicates that the second layer does not exist. The case where "-" is recorded in the "Thickness [μm]" column of "Third Layer" in Table 2 indicates that the third layer does not exist.
[0291] <Measurement of λ2 / λ1>
[0292] For the cutting tool of each sample, λ2 / λ1 was calculated by the method described in the first embodiment. The obtained results are recorded in the "λ2 / λ1" column of Table 1. It should be noted that the case where "-" is recorded in the "λ2 / λ1" column of Table 1 indicates that at least one of the first unit layer and the second unit layer does not exist.
[0293] <Measurement of Crystal Structure of First Unit Layer>
[0294] For the cutting tool of each sample, XRD measurement is performed on the first unit layer to confirm whether the first unit layer has a hexagonal crystal structure. The specific method is as described in the first embodiment. The results are shown in the "Hexagonal Crystal Structure" column of the "First Unit Layer" in Table 1. The record of "Yes" indicates that the first unit layer has a hexagonal crystal structure, and the record of "No" indicates that the first unit layer does not have a hexagonal crystal structure. It should be noted that when the crystal structure of the second unit layer was measured, it was confirmed that in all samples, the second unit layer contained a cubic crystal structure.
[0295] <Measurement of Hardness of Film>
[0296] In Samples 1 to 25, the hardness of the coating was measured by the method described in the first embodiment. It was confirmed that the hardness of the coating of these samples was within the range of 30 GPa or more and 55 GPa or less.
[0297] <Cutting test 1: Continuous turning test>
[0298] For each sample CNMG120408-shaped cutting tool, a dry continuous turning test was performed under the following cutting conditions, and the time until the flank wear of the tool tip reached 0.2 mm was measured. The results are recorded in the "Cutting time [minutes]" column of Table 2. A longer cutting time means a longer tool life.
[0299] 《Cutting conditions》
[0300] ·Material to be cut: SCM440 (HB=300)
[0301] Cutting speed: 260m / min
[0302] Feed speed: 0.3mm / rev
[0303] ·Incision: 2.0mm
[0304] Coolant: Dry
[0305] The cutting process performed under the above-mentioned cutting conditions is high-speed and high-efficiency machining of difficult-to-cut materials, and is equivalent to cutting processing performed under the condition of high tool tip temperature.
[0306] The cutting tools of samples 1 to 25 correspond to the examples, and the cutting tools of samples 101 to 106 correspond to the comparative examples. It was confirmed that the cutting tools of samples 1 to 25 had longer tool life than the cutting tools of samples 101 to 106 in cutting processes performed under conditions of high tool edge temperatures.
[0307] <Cutting test 2: Milling test>
[0308] For each sample of the SEMT13T3AGSN shaped cutting tool, the center line of the plate with a width of 150 mm made of a difficult-to-cut material and the width of the plate wider than the center line of the plate are aligned. The center of the tool was aligned, and surface milling was performed under the following cutting conditions. The cutting length until the flank wear of the tool tip reached 0.2 mm was measured. The results are recorded in the "Cutting Length [km]" column of Table 2. A longer cutting length means a longer tool life.
[0309] 《Cutting conditions》
[0310] Cutting material: SKD11 (HB = 235)
[0311] Cutting speed: 190m / min
[0312] Feed speed: 0.15mm / t
[0313] Axial incision ap: 1.5mm
[0314] Radial cut ae: 150mm
[0315] Coolant: Dry
[0316] The cutting process performed under the above-mentioned cutting conditions is a high-speed and high-efficiency milling process of difficult-to-cut materials under dry conditions, which is equivalent to a cutting process performed under conditions where the tool tip temperature is high.
[0317] The cutting tools of samples 1 to 25 correspond to the examples, and the cutting tools of samples 101 to 106 correspond to the comparative examples. It was confirmed that the cutting tools of samples 1 to 25 had longer tool life than the cutting tools of samples 101 to 106 in cutting processes performed under conditions of high tool edge temperatures.
[0318] [Example 2]
[0319] <Samples 51 to 85, Samples 151 to 176>
[0320] 《Manufacturing of cutting tools》
[0321] The substrates of each sample were prepared by the same method as in Example 1. While the substrate was rotated at the center, argon gas and nitrogen gas were introduced as reaction gases, and while the temperature of the substrate was maintained at 450°C, the reaction gas pressure was maintained at 2.0 Pa, and the voltage of the bias power supply 110 was maintained at a predetermined constant value in the range of -50V to -200V, an arc current of 100A was supplied to the cathode 106 and the cathode 107, respectively, thereby generating metal ions from the cathode 106 and the cathode 107, and forming the 2A layer and the 1A layer having the composition shown in Tables 3 to 6 on the substrate. The composition of the cathode 106 was adjusted in such a way as to obtain the composition of the first unit layer of Tables 3 to 4. In addition, the composition of the cathode 107 was adjusted in such a way as to obtain the composition of the third unit layer of Tables 3 to 4. The composition of the cathode 120 was adjusted in such a way as to obtain the composition of the 3A layer of Tables 5 to 6. In the manufacturing method disclosed in the present invention, the temperature of the substrate is 450°C, which is lower than the formation temperature of the existing nitride film of 600°C. The reason is as follows. The inventors of the present invention have found that when the temperature of the substrate is set to 600°C for film formation, there is a tendency for the hardness of the coating to decrease. The reason for this has been studied, and it is speculated that when the temperature of the substrate is set to 600°C for film formation, the carbon (C) contained in the cathode used for the first unit layer becomes free carbon and precipitates in the formed coating. As a result of in-depth research by the inventors of the present invention, it was found that by setting the temperature of the substrate to 450°C for film formation, excellent hardness can be maintained even at high temperatures, forming a coating with excellent wear resistance.
[0322] In the case where the 2A layer is formed, the 1A layer is formed by alternately stacking the first unit layer and the third unit layer on the 2A layer by the number of stackings shown in Tables 3 to 4. In the case where the 2A layer is not formed, the 1A layer is formed by alternately stacking the first unit layer and the third unit layer on the substrate by the number of stackings shown in Tables 3 to 4. In addition, the thickness of the 2A layer, the thickness of each of the first unit layer and the third unit layer in the 1A layer, and the number of stackings are adjusted by the rotation speed of the substrate. Then, when the thickness of the 2A layer and the 1A layer reaches the thickness shown in Tables 3 to 6, respectively, the current supplied to the evaporation source is stopped.
[0323] Next, while introducing argon, nitrogen, and methane as reaction gases into the chamber 101, an arc current of 100A was supplied to the cathode 120 while maintaining the temperature of the substrate at 350°C, the reaction gas pressure at 2.0 Pa, and the voltage of the bias power supply 110 at -350V, thereby generating metal ions from the cathode 120 and forming the 3A layer on the 1A layer. When the thickness of the 3A layer reached the thickness shown in Tables 5 and 6, the current supplied to the evaporation source was stopped. The amount of nitrogen gas introduced and the amount of methane gas introduced were adjusted in such a way as to obtain the composition of the 3A layer in Tables 5 and 6. In the above manner, cutting tools of various samples were produced.
[0324] Table 3
[0325]
[0326] Table 4
[0327]
[0328] Table 5
[0329]
[0330] Table 6
[0331]
[0332] "evaluate"
[0333] For the cutting tools involved in each sample, the composition of the first unit layer, the composition of the third unit layer, the composition of the 2A layer, the composition of the 3A layer, the number of stacking of the first unit layer and the third unit layer, the average thickness of the first unit layer, the average thickness of the third unit layer, the thickness of the 1A layer, the thickness of the 2A layer, the thickness of the 3A layer, λ3 / λ1, the crystal structure of the first unit layer, and the hardness of the coating were measured. The measuring method of each item is as described in Example 1. The results are shown in Tables 3 to 6.
[0334] <Measurement of Hardness of Film>
[0335] In samples 51 to 85, the hardness of the coating was measured by the method described in the first embodiment. It was confirmed that the hardness of the coating of these samples was within the range of 30 GPa or more and 55 GPa or less.
[0336] <Cutting test 3: Continuous turning test>
[0337] For each sample CNMG120408-shaped cutting tool, a dry continuous turning test was performed under the following cutting conditions, and the time until the flank wear of the tool tip reached 0.2 mm was measured. The results are recorded in the "Cutting Time [minutes]" column of Tables 5 and 6. In addition, in Tables 5 and 6, a long cutting time means a long tool life.
[0338] (Cutting conditions)
[0339] ·Material to be cut: Inconel 718 (aging material: HB = 400)
[0340] Cutting speed: 70m / min
[0341] Feed speed: 0.15mm / rev
[0342] ·Incision: 1.0mm
[0343] Coolant: Dry
[0344] The cutting process performed under the above-mentioned cutting conditions is high-speed and high-efficiency machining of difficult-to-cut materials, and is equivalent to cutting processing performed under the condition of high tool tip temperature.
[0345] The cutting tools of samples 51 to 85 correspond to the examples, and the cutting tools of samples 151 to 176 correspond to the comparative examples. It was confirmed that the cutting tools of samples 51 to 85 had longer tool life than the cutting tools of samples 151 to 176 in cutting processes performed under conditions of high tool edge temperatures.
[0346] <Cutting test 4: Milling test>
[0347] For each sample of the SEMT13T3AGSN shaped cutting tool, the center line of the plate with a width of 150 mm made of a difficult-to-cut material and the width of the plate wider than the center line of the plate are aligned. The center of the tool was aligned, and surface milling was performed under the following cutting conditions. The cutting length until the flank wear of the tool tip reached 0.2 mm was measured. The results are recorded in the "Cutting Length [km]" column of Tables 5 and 6. It should be noted that in Tables 5 and 6, a long cutting length means a long tool life.
[0348] 《Cutting conditions》
[0349] ·Material to be cut: FCD700 (HB=250)
[0350] Cutting speed: 260m / min
[0351] Feed speed: 0.2mm / t
[0352] Axial incision ap: 2.0mm
[0353] Radial cut ae: 150mm
[0354] Coolant: Dry
[0355] The cutting process performed under the above-mentioned cutting conditions is a high-speed and high-efficiency milling process of difficult-to-cut materials under dry conditions, which is equivalent to a cutting process performed under conditions where the tool tip temperature is high.
[0356] The cutting tools of samples 51 to 85 correspond to the examples, and the cutting tools of samples 151 to 176 correspond to the comparative examples. It was confirmed that the cutting tools of samples 51 to 85 had longer tool life than the cutting tools of samples 151 to 176 in cutting processes performed under conditions of high tool edge temperatures.
[0357] As mentioned above, although the embodiment and the example of this disclosure were described, it is also planned from the beginning that the configurations of each embodiment and the example described above are appropriately combined or variously modified.
[0358] The embodiments and examples disclosed herein are illustrative in all aspects and are not restrictive. The scope of the present invention is indicated by the claims rather than the embodiments and is intended to include all modifications within the scope and meaning equivalent to the claims.
[0359] Description of Reference Numerals
[0360] 1: cutting tool; 2: substrate; 3: coating; 12: first unit layer; 13: first layer; 13A: 1A layer; 14: third layer; 14A: 3A layer; 15: second unit layer; 16: second layer; 16A: 2A layer; 17: third unit layer; 101: chamber; 102: gas; 103: gas exhaust port; 104: substrate holder; 105: gas inlet port; 106, 107, 120: cathode; 108, 109: arc power supply; 110: bias power supply.
Claims
1. A cutting tool comprising a substrate and a coating disposed on the substrate, wherein: The coating comprises a first layer, The first layer is composed of alternating layers formed by alternatingly stacking first unit layers and second unit layers, The first unit layer has a hexagonal crystal structure, The first unit layer is composed of W(C 1-a N a ) x constitute, The a is greater than or equal to 0.3 and less than or equal to 0.8, The x is greater than or equal to 0.8 and less than or equal to 1.2, The second unit layer is composed of Al c V 1-c N constitutes, The c is greater than or equal to 0.40 and less than or equal to 0.
80.
2. The cutting tool according to claim 1, wherein: In the first unit layer and the second unit layer adjacent to the first unit layer, a ratio λ2 / λ1 of a thickness λ2 μm of the second unit layer to a thickness λ1 μm of the first unit layer is greater than or equal to 1.0 and less than or equal to 5.
0.
3. The cutting tool according to claim 1 or 2, wherein: The average thickness of the first unit layer is greater than or equal to 0.002 μm and less than or equal to 0.2 μm, The average thickness of the second unit layer is greater than or equal to 0.002 μm and less than or equal to 0.2 μm.
4. The cutting tool according to any one of claims 1 to 3, wherein: The coating further includes a second layer disposed between the substrate and the first layer. The composition of the second layer is the same as the composition of the first unit layer or the composition of the second unit layer.
5. The cutting tool according to claim 4, wherein: The composition of the second layer is the same as that of the first unit layer, The second layer is thicker than the first unit layer.
6. The cutting tool according to claim 4, wherein: The composition of the second layer is the same as the composition of the second unit layer, The second layer has a thickness greater than that of the second unit layer.
7. The cutting tool according to any one of claims 1 to 6, wherein: The coating further includes a third layer disposed on the first layer on the opposite side of the substrate. The third layer is composed of AlVCN.
8. A cutting tool comprising a substrate and a coating disposed on the substrate, wherein: The coating comprises a layer 1A, The 1A layer is composed of an alternating layer in which the first unit layer and the third unit layer are alternately stacked. The first unit layer has a hexagonal crystal structure, The first unit layer is composed of W(C 1-a N a ) x constitute, The a is greater than or equal to 0.3 and less than or equal to 0.8, The x is greater than or equal to 0.8 and less than or equal to 1.2, The third unit layer is composed of Al d V 1-d-e M e N constitutes, The M is silicon, boron, yttrium, cerium or lanthanum, The d is greater than or equal to 0.40 and less than or equal to 0.80, The above-mentioned e is greater than 0 and less than 0.
05.
9. The cutting tool according to claim 8, wherein: In the first unit layer and the third unit layer adjacent to the first unit layer, A ratio λ3 / λ1 of a thickness λ3 μm of the third unit layer to a thickness λ1 μm of the first unit layer is greater than or equal to 1.0 and less than or equal to 5.
0.
10. The cutting tool according to claim 8 or 9, wherein: The M is silicon.
11. The cutting tool according to claim 8 or 9, wherein: The M is boron.
12. The cutting tool according to any one of claims 8 to 11, wherein: The average thickness of the first unit layer is greater than or equal to 0.002 μm and less than or equal to 0.2 μm, The average thickness of the third unit layer is greater than or equal to 0.002 μm and less than or equal to 0.2 μm.
13. The cutting tool according to any one of claims 8 to 12, wherein: The coating further includes a 2A layer disposed between the substrate and the 1A layer, The composition of the 2A layer is the same as the composition of the first unit layer or the composition of the third unit layer.
14. The cutting tool according to claim 13, wherein: The composition of the 2A layer is the same as that of the first unit layer, The thickness of the 2A layer is thicker than that of the first unit layer.
15. The cutting tool according to claim 13, wherein: The composition of the 2A layer is the same as the composition of the third unit layer, The thickness of the 2A layer is thicker than that of the third unit layer.
16. The cutting tool according to any one of claims 8 to 15, wherein: The coating further includes a 3A layer provided on the side of the 1A layer opposite to the substrate, The 3A layer is composed of AlVMeCN, The Me is silicon, boron, yttrium, cerium or lanthanum.
Citation Information
Patent Citations
Vanadium Aluminum Nitride (VAIN) Micro-Alloyed with Ti and / or Si
JP2022512808A